Spatial correlation analysis of air pollution and respiratory diseases period 2013-2022 (Tabriz City) - Maryam Alsadat Heshmati; Mohammad Ebrahim Ramazani; Ziba Beheshti (آلودگی‌های محیطی و توسعه پایدار شهری)
Recent epidemiological studies worldwide have investigated the relationship between air pollution and human health, revealing a significant impact of increased air pollution on respiratory tract infections. Tabriz, one of the most polluted cities in the country, faces serious health threats due to air pollution. The present study aimed to determin the relationship between different factors of air pollution and the incidence of asthma in Tabriz. Statistical data on pollutants (suspended particles with a diameter of less than 10 microns (PM10), ozone (O3), sulfur dioxide (SO2), nitrogen dioxide (NO2), and carbon monoxide (CO)) from 2013 to 2022, were collected from five air pollutant measurement stations. ARC GIS software was used to analyze and compare the collected data with standard air pollution index (PSI). The results of the research indicated that the concentration of pollutants is low, medim and high in the regions 1, 10 and 4, respectively. The results indicated that there is a direct spatial relationship between SO2 levels and asthma incidence. Additionally, the highest O3 concentrations were in the western side and part of the city center, correlating with higher number of asthma cases, indicating a direct spatial relationship between O3 concentration and athma incidence. PM10 pollution was higher in the city center, where the highest frequency of asthma patients was observed, showing a direct spatial relationship between PM10 and asthma prevalence.